2022
DOI: 10.21203/rs.3.rs-1658198/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-inflammatory effects of Irisin in LPS-stimulated RAW264.7 macrophages by inhibiting the MAPK pathway

Abstract: Aims Irisin is a newly discovered actin that has been shown to be effective against inflammation-related symptoms. The aim of this study was to investigate the influence of Irisin on LPS-induced inflammation in vitro and to investigate the role of the mitogen-activated protein kinase (MAPK) pathway in the protecting effect of Irisin in LPS-stimulated RAW 264.7 macrophages.Methods Cell viability was assessed using MTT assay and flow cytometry, cell morphology was measured by optical microscope, IL-12 and IL-23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Deletion and overexpression of irisin has been shown to exacerbate and ameliorate cardiac hypertrophy in rats with hypertension, respectively (45). As sotalol and pirinixic acid treatment both upregulate irisin expression, and pirinixic acid has hypertension mediating effects, it is probable that sotalol also exhibits anti-hypertensive properties (46; 47).…”
Section: Resultsmentioning
confidence: 99%
“…Deletion and overexpression of irisin has been shown to exacerbate and ameliorate cardiac hypertrophy in rats with hypertension, respectively (45). As sotalol and pirinixic acid treatment both upregulate irisin expression, and pirinixic acid has hypertension mediating effects, it is probable that sotalol also exhibits anti-hypertensive properties (46; 47).…”
Section: Resultsmentioning
confidence: 99%
“…In an experimental animal model of ulcerative colitis, it has been found that exogenous irisin modulates the intestinal microbiota (by altering the diversity of microorganisms in the stool) and suppresses inflammation in the intestinal mucosa, indicating that irisin has anti-inflammatory properties[ 13 ]. It has been suggested that the anti-inflammatory effects of irisin are related to the inhibition of cytotoxicity and apoptosis via inhibiting the mitogen-activated protein kinase pathway[ 14 ]. The sports activity is a barrier for patients with active Crohn’s disease (intestinal manifestations) because it flares up the symptoms[ 15 ].…”
Section: To the Editormentioning
confidence: 99%